Flow: Currents of Change in our river landscapes : For the Great Benefit Of Us All, 2024 - Härkönen, Elina (Lapin yliopisto, 2024)
My work is an examination about the concrete wall of a hydropower plant’s dam. It is a kind of an escape, a way around the heaviness of things. After learning about the communal trauma of the building of reservoirs Lokka and Porttipahta in northern Finland, sadness and powerlessness became an all-encompassing feeling. The building and harnessing of the reservoirs and rivers was justified as the benefit of the whole nation of Finland in the 1950s. In the bill, the exploitation of Lapland’s natural resources and the taking over of “empty land” were seen as necessary. It was however admitted that sacrifices had to be made. The magnitude of these sacrifices were beyond comprehension and nowadays it is considered a violation of human rights. Not to mention the extensive loss of fauna and flora of the area. My experiences at the dams were suffocating. The only way to deal with it was to concentrate on the details and consider the effect of time on concrete as a human construction. To look at them as if from the outside helped, simultaneously knowing that I too have benefited from the construction of these dams.